The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.2458/azu_jrm_v53i6_clary
|View full text |Cite
|
Sign up to set email alerts
|

Stubble height as a tool for management of riparian areas

Abstract: Stubble height, a measure of the herbaceous vegetation remaining after grazing, has been widely used in recent years to gage the impacts of grazing use in riparian areas. Stubble height is a short-term management guide that should only be applied to help attain long-term ecological objectives; it should not be thought of as a long-term management objective.Maintaining a minimum stubble height helps preserve forage plant vigor, retain sufficient forage to reduce cattle browsing of willows (Salix spp.), stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 43 publications
1
71
0
Order By: Relevance
“…m 21 stream during the approximately 60 d between measurements from May through November or the approximately 180 d between measurements in November and May or 6.52 cow-days ? m 21 stream annually would result in a sward height less than the 10 cm needed to protect against soil detachment during precipitation and treading events (Clary and Leininger 2000). Although the use of stubble height alone has been reported to be not suitable to predict sediment infiltration (Pearce et al 1997, Haan et al (2006) reported lower quantities and phosphorus loading of runoff from pastures that were rotationally stocked to a residual height of 10 cm than in pastures continuously stocked to a residual height of 5 cm in cool-season grass pastures.…”
Section: Forage Sward Heightmentioning
confidence: 99%
See 2 more Smart Citations
“…m 21 stream during the approximately 60 d between measurements from May through November or the approximately 180 d between measurements in November and May or 6.52 cow-days ? m 21 stream annually would result in a sward height less than the 10 cm needed to protect against soil detachment during precipitation and treading events (Clary and Leininger 2000). Although the use of stubble height alone has been reported to be not suitable to predict sediment infiltration (Pearce et al 1997, Haan et al (2006) reported lower quantities and phosphorus loading of runoff from pastures that were rotationally stocked to a residual height of 10 cm than in pastures continuously stocked to a residual height of 5 cm in cool-season grass pastures.…”
Section: Forage Sward Heightmentioning
confidence: 99%
“…Although the use of stubble height alone has been reported to be not suitable to predict sediment infiltration (Pearce et al 1997, Haan et al (2006) reported lower quantities and phosphorus loading of runoff from pastures that were rotationally stocked to a residual height of 10 cm than in pastures continuously stocked to a residual height of 5 cm in cool-season grass pastures. By maintaining adequate vegetation cover and height, plant vigor may be preserved (Frazier et al 1998;Clary and Leininger 2000) and reduce NPS pollution from riparian areas of pastures (Warren et al 1986;Elliott et al 2002;Reed and Carpenter 2002). In the current study, forage sward heights within riparian areas of pastures quadratically increased as the proportion of reed canarygrass increased y~4:06z0:40x{0:0027x 2 r 2~0 :42…”
Section: Forage Sward Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect effects of livestock on water quality include impacts to streamside plant communities and physical damage to streambanks. Riparian vegetation plays a critical role in sustaining the biotic integrity of the stream ecosystem by anchoring bank material in place during high flow events (Kleinfelder et al, 1992;Clary and Leininger, 2000). Livestock grazing of this resource is generally sustainable under conditions of moderate utilization (e.g., graze to 10cm stubble height; Boyd and Svejcar, 2004;Volesky et al, 2011), but timing of grazing can also influence livestock impacts on water quality and riparian vegetation (Boyd and Svejcar, 2004).…”
Section: Modern Agriculture and Water Quality Of Free-flowing Streamsmentioning
confidence: 99%
“…Maintaining optimum pasture cover and allowing litter to accumulate on the soil surface can preserve forage plant vigor, improve soil structure, stabilize sediment, and reduce the movement of nutrients from pastures into streams (Naeth et al 1991b(Naeth et al , 1996Clary and Leininger 2000). Rotational stocking systems and hay harvest have been shown to reduce the amount of bare ground and maintain an adequate forage canopy in pastures, as opposed to continuous stocking, so that excessive soil erosion and nutrient transport to surface waters are prevented (Gilley et al 1996;Manley et al 1997).…”
Section: Introductionmentioning
confidence: 99%